Rancang Bangun Manajemen Aset Laboratorium Sistem Informasi FMIPA Untan Berbasis Website - Ferdy Febriyanto; Renny Puspita Sari (Sekawan Institut, 2026)
This study aims to design and build a website-based laboratory asset management information system at the Information Systems Department, Faculty of Mathematics and Natural Sciences, Tanjungpura University. The main problem with the current system is that the asset management process is still carried out manually, resulting in delays in recording, potential data errors, and limited access to information. In addition, the lack of an integrated system capable of supporting real-time asset management indicates a gap between the need for effective asset management and current system capabilities. The system development method used is the Fountain Model, which is iterative and flexible in supporting the software design and development process. System evalua-tion was conducted using the Black-Box Testing method to assess the suitability of system func-tions, and the System Usability Scale (SUS) to measure system usability from the user perspective. The test results showed that all system features run according to the functional requirements, with no critical errors found during Black Box testing. In addition, the evaluation results using the SUS method yielded a score of 82.5, which falls within the excellent category and indicates that the sys-tem is easy to use and acceptable to users. The implementation of this system also improved the ef-ficiency of the asset management process, sped up data retrieval, and reduced the risk of recording errors compared to the previous manual system. Thus, the developed information system not only addresses asset management problems but also improves service quality and data-driven deci-sion-making in the laboratory environment.